2019
DOI: 10.1177/1475921719869986
|View full text |Cite
|
Sign up to set email alerts
|

Real-time strain monitoring and damage detection of composites in different directions of the applied load using a microscale flexible Nylon/Ag strain sensor

Abstract: Composites are prone to failure during operating conditions and that is why vast research studies have been carried out to develop in situ sensors and monitoring systems to avoid their catastrophic failure and repairing cost. The aim of this research article was to develop a flexible strain sensor wire for real-time monitoring and damage detection in the composites when subjected to operational loads. This flexible strain sensor wire was developed by depositing conductive silver (Ag) nanoparticles on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, an important advantage in the preparation of PP/CNT strain-sensors lies in their flexibility. As reported elsewhere, it is important to have flexible strain-sensors in order to be easily used in several fields of application [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an important advantage in the preparation of PP/CNT strain-sensors lies in their flexibility. As reported elsewhere, it is important to have flexible strain-sensors in order to be easily used in several fields of application [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…After that, reduction process in ammonia (NH 3 ) environment was carried out for a period of 2 hours which reduced the Ag(I) to Ag(0) ions and finally, silver nanoparticles were deposited on the surface of nylon. Scanning electron microscopy (SEM) further verified the homogeneous deposition of Ag nanoparticles on every filament of the Nylon yarn [64], Figure 2. Then the fiber sensor was cut into specific length and was inserted between the plies of chopped glass fibers in their respective position and direction during the fabrication of the composite specimen.…”
Section: A Fabrication Proceduresmentioning
confidence: 82%
“…However, application of Ag coated fabric regarding SHM of composites is still limited. Y. Qureshi et al [62,63] recently investigated the application of Ag coated nylon yarn as strain sensor under tensile loading and found that the position of Nylon/Ag sensor wire played an important part in identification of type of strain and damage [64]. Moreover, they also found out in their extended study that position of Nylon/Ag sensor wire, at different locations through thickness in respective specimens but in same direction, differentiated in type of strain and damage in each specimen subjected to flexural loading up to fracture [65].…”
Section: Introductionmentioning
confidence: 99%
“…Qureshi et al [92] have shown that silver coated nylon yarns can be used as strain sensors within GFRPs. They coated nylon yarns with silver nano-particles and placed them within the GFRPs during manufacturing.…”
Section: Summary Of Mechanisms Of Conductivity Improvementmentioning
confidence: 99%